The Branding of Jember Tape Chips Products Through Audio Visual Ads - Fajar Aji; Dwi Haryanto (LP2M Universitas Jember, 2019)
Jember is a district with the geographical conditions of mountains, agriculture, and plantations. The connection between these three characteristics gave birth to a diversity of arts, languages, tourism, and culinary. Utilization of the agricultural sector, especially in the Ajung sub-district, there are people in this area who rely heavily on natural resources, especially in agricultural and plantation resources. This beneficial natural potential makes the people in Ajung Subdistrict, especially in Pancakarya Village, much to build a home industry for processing agricultural products in the form of tape industry. The problem faced by partners is the lack of familiarity of products that are widely owned, thus causing the partner's economy to not be optimal. This problem is the basis of the service program proposed by the proponent to strive to increase the marketing of tape chips. Based on the specific targets to be achieved, the main purpose of the community service activities proposed is to strengthen the brand image of the chips product through audio-visual advertising. The method of implementing this service program is adjusted to the standard operating procedure for making audiovisual works consisting of stages: 1) pre-production consisting of idea-finding, planning, and preparation; 2) production; and 3) post-production. The results of audio-visual advertising of tape chips are expected to be a promotional media for products owned by Koplak Food Homemade Industry so that they can be widely known to the public and build brand image products for tape chips.